A fibrous morphology silica-CoFe2O4 nanocarrier for anti-cancer drug delivery. Issue 2 (1st February 2018) - Fan, Huitao; Li, Bo; Shi, Zhenzhen; Zhao, Ling; Wang, Kun; Qiu, Dongfang
Abstract: Magnetic CoFe2 O4 nanoparticles were encapsulated with fibrous silica shells via a simple self-assembly process to fabricate a novel, bifunctional, nanocomposite of fibrous-structured silica-CoFe2 O4 . The nanocomposite not only exhibited fibrous spherical morphology, typical mesoporous structure, high specific surface area and narrow size distribution, but also excellent superparamagnetic features and good monodispersity. Further study demonstrated that doxorubicin hydrochloride could be easily loaded onto the CoFe2 O4 @FMS (fibrous morphology silica) nanoplatforms and released with pH stimuli. Additionally, MTT assay confirmed that CoFe2 O4 @FMS NPs have good biocompatibility. Therefore, a novel nanocarrier based on CoFe2 O4 @FMS is proposed, with potential application for targeted cancer therapy. Graphical abstract: Bifunctional nanocomposites of mesoporous silica-CoFe2 O4 with fibrous morphology displayed excellent loading and controlled release of DOX. fx1 Highlights: A fibrous morphology silica-CoFe2 O4 nanocarrier were successfully synthesized. The nanocomposite exhibits typical mesoporous structure and excellent superparamagnetic features. DOX could be easily loaded onto the CoFe2 O4 @FMS nanoplatforms and released with pH stimuli.